Current status of the multinational Arabidopsis community. (2nd August 2020) - Parry, Geraint; Provart, Nicholas J.; Brady, Siobhan M.; Uzilday, Baris; ,
Abstract: The multinational Arabidopsis research community is highly collaborative and over the past thirty years these activities have been documented by the Multinational Arabidopsis Steering Committee (MASC). Here, we (a) highlight recent research advances made with the reference plant Arabidopsis thaliana ; (b) provide summaries from recent reports submitted by MASC subcommittees, projects and resources associated with MASC and from MASC country representatives; and (c) initiate a call for ideas and foci for the "fourth decadal roadmap, " which will advise and coordinate the global activities of the Arabidopsis research community.